2009
DOI: 10.1016/j.susc.2008.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Ag–Cu alloy surfaces in an oxidizing environment: A first-principles study

Abstract: Recent experiments on model catalysts have shown that Ag-Cu alloys have improved selectivity with respect to pure silver for ethylene epoxidation. In this paper we review our first-principles investigations on the (111) surface of this alloy and present new findings on other low index surfaces.We find that, for every surface orientation, the presence of oxygen leads to copper segregation to the surface. Considering the alloy to be in equilibrium with an oxygen atmosphere and accounting for the effect of temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 55 publications
2
50
0
Order By: Relevance
“…The formation of the CuO-like layer is in agreement with theoretical work that has predicted bulk copper oxides are stable at high copper concentrations. 10 This finding also explains the plateau in selectivity observed by Linic et. al.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The formation of the CuO-like layer is in agreement with theoretical work that has predicted bulk copper oxides are stable at high copper concentrations. 10 This finding also explains the plateau in selectivity observed by Linic et. al.…”
Section: Discussionsupporting
confidence: 55%
“…If the surface were truly to remain metallic under epoxidation conditions, with Cu atoms distributed over the surface, the Cu concentration and O chemical potentials would need to be extremely low. 10 It is therefore likely that either the surface is completely coated with some form of oxidized copper, or all the Cu has segregated to Cu 2 O/CuO regions, leaving regions of pure Ag behind. This scenario is depicted in Figure 9 D. If this were the case, then what role would copper play?…”
Section: Discussionmentioning
confidence: 99%
“…The on average rather Ir-rich surface composition observed in the as-prepared sample reects the preferential surface conguration of this alloy under vacuum conditions, which can be rationalised by the lower surface energy of Ir as compared to Ru. 48,49 In the presence of a gaseous adsorbate, it is known that the surface compositions of alloys can substantially change, or be inverted, 35,[50][51][52] as discussed below.…”
Section: Validation Of Proposed Experimental Protocolmentioning
confidence: 99%
“…Using the ab initio atomistic thermodynamics approach, Piccinin et al have studied the surface structure of the Ag-Cu alloy in the presence of oxygen. [40][41][42] They have shown that the strength of Cu-O bond relative to the Ag-O bond drives the segregation of Cu to the surface. Their main finding is that under conditions of pressure and temperature relevant for ethylene epoxidation, a thin copper-oxide-like layer is predicted to form at the surface.…”
Section: Selected Theoretical Studies Of Bi-metallic Alloys In An Oxymentioning
confidence: 99%